Copra master collection, book one ebook - Fiffe, Michel (Copra (2012)., 2022)
They're ugly. They're mean. But up until today, they've always been loyal. So when one of their own betrays them, COPRA has no choice but to turn their nightmarish skills back on everyone who ever even looked at them funny.